Registration of 'Lanning' Hard Red Spring Wheat. Issue 3 (30th August 2016) - Heo, H.-Y.; Lanning, S. P.; Lamb, P. F.; Nash, D.; Wichman, D. M.; Kephart, K. D.; Stougaard, R. N.; Miller, J.; Reddy, G.V.P.; Chen, C.; Eckhoff, J. L.; Grey, W. E.; et al.
Abstract : 'Lanning' hard red spring wheat (Reg. No. CV‐1120, PI 676978) ( Triticum aestivum L.) was released by the Montana Agricultural Experiment Station due to its excellent yield potential in dryland areas of Montana and its superior end‐use quality. Lanning was derived from the cross 'Glenn'/MT0747 by single seed descent beginning in the F2 generation. A single plant in the F4 generation was the source of experimental line MT1316, which subsequently was named Lanning. Lanning has grain yield equivalent to 'Vida', the most widely grown cultivar in Montana from 2010 to 2015. Lanning has higher grain protein and stronger gluten characteristics than Vida. Lanning is hollow stemmed, suggesting that it will be susceptible to damage caused by the wheat stem sawfly ( Cephus cinctus Nort.). Lanning should be of interest to producers of hard red spring on dryland acreage throughout the wheat‐growing region of Montana.